Neural, Cellular and Molecular Mechanisms of Active Forgetting - Medina, Jorge H. (Frontiers in Systems Neuroscience, 2018)
The neurobiology of memory formation attracts much attention in the last five decades. Conversely, the rules that govern and the mechanisms underlying forgetting are less understood. In addition to retroactive interference, retrieval-induced forgetting and passive decay of time, it has been recently demonstrated that the nervous system has a diversity of active and inherent processes involved in forgetting. In drosophila, some operate mainly at an early stage of memory formation and involves dopamine neurons, specific postsynaptic dopamine receptor subtypes, Rac1 activation, and induces rapid active forgetting. In mammals, others regulate forgetting and persistence of seemingly consolidated memories and implicate the activity of dopamine receptor subtypes and AMPA receptors in the hippocampus and related structures to activate parallel signaling pathways controlling active time-dependent forgetting. Most of them may involve plastic changes in synaptic and extrasynaptic receptors including specific removal of GluA2 AMPA receptors. Forgetting at longer timescales might also include changes in adult neurogenesis in the dentate gyrus of the hippocampus. Therefore, based on relevance or value considerations neuronal circuits may regulate in a time-dependent manner what is formed, stored, and maintained and what is forgotten.